2020
DOI: 10.4236/oalib.1106072
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Price and Exchange Rate Nexus: An Ardl Bound Approach

Abstract: This study investigates the impact of crude oil price on exchange rate in Nigeria using an autoregressive distributed lag (ARDL) model covering the period from 1983-2017. The results showed that crude oil price has negative and significant impact on exchange rate in both the long run and the short run whereas oil revenue and Gross Domestic Products have significant positive impact on exchange rate also in both the long-run and the short-run periods. The findings suggested that crude oil price which is the foca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In contrast, the negative bubble during the COVID-19 outbreak is associated with downwardly accelerating price decreases in the WTI and Brent crude oil prices. This result largely confirms the findings of the previous studies of Musa et al (2020) , Ali et al (2020) , Shu et al (2021) . Weng et al (2021) find that COVID-19 related news affects the price of crude oil futures, which has a certain explanatory power for the volatility of crude oil futures.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, the negative bubble during the COVID-19 outbreak is associated with downwardly accelerating price decreases in the WTI and Brent crude oil prices. This result largely confirms the findings of the previous studies of Musa et al (2020) , Ali et al (2020) , Shu et al (2021) . Weng et al (2021) find that COVID-19 related news affects the price of crude oil futures, which has a certain explanatory power for the volatility of crude oil futures.…”
Section: Resultssupporting
confidence: 92%
“…16 found different degrees of heterogeneity in the impact of oil price shocks on different industries through a study of OECD countries, which also found that all oil price increases have a negative impact on economic activity. 22 However, 14 calculated the direct and complete consumption coefficients for the coal industry and other sectors of the national economy through an input-output model and analyzed the response of each sector to coal price fluctuations. The study shows that fluctuations in coal prices have the greatest impact on the industrial sectors such as electricity, production industries and thermal power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we need to construct VAR models and use the AIC and the SIC to determine the maximum lag order of the models. 22 In Table 4 we refer to these two criteria and choose the maximum lag order as p = 2. Furthermore, if all the variables are stationary at I(0) or I(1), the bounds testing approach would be used and are the major advantages of using the ARDL estimators.…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have contributed to the This Journal is licensed under a Creative Commons Attribution 4.0 International License literature on the relationship between oil prices and economic and financial variables, starting with the work of Hamilton (1983). Sadorsky (1999), Basher and Sadorsky (2006), Park and Ratti (2008), Imarhiagbe (2010), Lee and Zeng (2011), Lee et al (2012), Syzdykova (2018) examining the relationship between oil prices and stock market index; Camarero et al (2002), Korhonen and Juurikkala (2009), Buetzer et al, (2012), Lin and Su, (2020), Musa et al (2020), Ding et al (2020) analyzing the relationship between oil prices and exchange rate, Lardic and Mignon (2008), Lescaroux and Mignon (2008), Mehrara andMohaghegh (2011), Hamilton (2012), Ashley and Tsang (2013), Maghyereh et al (2019), Mo et al (2019), van Eyden et al (2019, Maheu et al (2020) examined the relationship between oil prices and growth.…”
Section: Introductionmentioning
confidence: 99%